NEW METHOD FOR DETERMINING REACTION MECHANISM OF MOLTEN SALT SYNTHESIZING CERAMIC MATERIALS - Wang S.; Zhang L.; Bai Y. (My University, 2005)
The conductivity of eutectic NaOH-KOH melt at 350°C during synthesizing BaTiO3 from TiO2 and BaCO3 and the conductivity of eutectic LiCl-KCl melt at 600°C during synthesizing Bi2Ti2O7 from Bi2O3 and TiO2 were measured continually by the A. C impedance technique. The conductivity of eutectic NaOH-KOH melt after adding TiO2 and BaCO3 decreased 6% and 10%, respectively, and the conductivity of eutectic KCl-LiCl melt decreased 20.5% after adding Bi2O3 and increased evidently after further adding TiO2, which suggests that Bi2O3 reacted with the solvents and formed intermediates, the conductivity of the melt therefore decreased and then increased after the solvents were released after the adding TiO2 reacted with the intermediates. XRD results show that several intermediates are formed during synthesizing Bi2Ti2O7 from Bi2O3 and TiO2 in eutectic LiCl-KCl melt at 600°C. So conductivity variation of molten salt is useful information for the reaction kinetics, and AC impedance is an effective technique to characterize the mechanism of molten salt synthesis reaction. The reaction of synthesizing BaTiO3 in molten NaOH-KOH at 350°C is a simple one-step reaction, and the reaction of synthesizing Bi2Ti2O7 in molten KCl-LiCl at 600°C is a complicated reaction.
Keywords: CERAMIC MATERIALS; MOLTEN SALT SYNTHESIS; REACTION MECHANISM